Predicting Financial Well-Being in Millennial Workers: A Test of the Theory of Planned Behavior and the Role of Financial Literacy - Ignatius Jonathan; Eka Bertuah (Jurnal Manajemen Teori dan Terapan)
Objective: This study investigates the influence of applying the Theory of Planned Behavior and Financial Literacy on building Financial Well-Being in millennial workers.